PENERAPAN ENTREPRENEURIAL MARKETING DAN SOSIALISASI KEBIJAKAN PEMERINTAH PADA KELOMPOK WANITA TANI DI DESA CINTAWARGI, KABUPATEN KARAWANG - Danang Kusnanto; Novian Ekawaty; Solihin Sidik (Jurnal Abdi Insani, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors most affected by the Covid-19 outbreak, including MSMEs that are empowered by women. Declining sales, limited marketing reach and lack of access to information about various economic recovery policy programs that have been rolled out by the central and local governments are the problems found in the Independent Women Farmers Group (KWT) in Cintawargi Village. This community service program aims to facilitate the Independent Women Farmers Group (KWT) in developing its business through marketing, access to capital, and managerial capabilities with indicators in the form of capital growth, sales growth, increased profits, workforce growth, and marketing expansion. There are two methods of community service carried out, firstly conducting socialization discussing how entrepreneurial marketing strategies can be applied and how to access various government assistance programs for MSMEs. Second, provide assistance that focuses on how to improve business performance. The results of the service program in the implementation of the socialization were an increase in the knowledge of fostered partners on entrepreneurial marketing strategy materials by 40%, knowledge about government policies increased by 50%, knowledge about simple financial management in MSMEs increased by 60%, and knowledge about optimizing labor in MSMEs increased. 50%. The results of the assistance implementation are that product innovation becomes more attractive, data on business legality needs and product certification, media for digital marketing, simple financial reports for MSMEs, and more attractive packaging sticker designs. This community service program with the implementation of entrepreneurial marketing strategies and government policies has contributed to improving partner business performance.